The Unity of Thomas Southerne’s The Fatal Marriage: or, The Innocent Adultery: A Reconsideration - Krajník, Filip (FOCUS: Papers in English Literary and Cultural Studies, 2024)
The present study discusses Thomas Southerne’s tragicomedy The Fatal Marriage (1694), based on Aphra Behn’s earlier novella The History of the Nun (1688). Modern criticism has tended chiefly to point out the simplification of Behn’s main heroine in Southerne’s play, as well as Southerne’s introduction of the comical subplot that appears to be irrelevant to the main tragic story. The present essay defends the structure of Southerne’s piece, observing both ideological and artistic themes that permeate both plots and create a dramatic unity in Southerne’s work. The essay further argues that, in order to achieve this, Southerne’s play is informed not only by Behn’s prose text, but also by a number of tropes from Behn’s dramatic oeuvre, as well as by Boccaccio’s Decameron and Shakespeare’s great tragedies, which both enjoyed considerable popularity when The Fatal Marriage was originally staged.